(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The role of financial knowledge in the early age of investment is critical for building a strong foundation for financial security in the future. Developing financial literacy skills at a young age enables individuals to understand the importance of saving and investing, how to manage their money effectively, and how to make informed investment decisions. With the right financial knowledge, individuals can avoid costly mistakes and take advantage of investment opportunities that will help them achieve their long-term financial goals. Therefore, investing in financial education and empowering individuals to make informed financial decisions from a young age is essential for promoting financial wellness and security.